Impact of a History of Hypertension in Pregnancy on Later Diagnosis of Atrial Fibrillation - Scantlebury, Dawn C.; Kattah, Andrea G.; Weissgerber, Tracey L.; Agarwal, Sanket; Mielke, Michelle M.; Weaver, Amy L.; Vaughan, Lisa E.; Henkin, Stanislav; Zimmerman, Katherine; Miller, Virginia M.; White, Wendy M.; Hayes, Sharonne N.; et al. (Journal of the American Heart Association, 2018)
Background Atrial fibrillation/flutter (AF) produces significant morbidity in women and is typically attributed to cardiac remodeling from multiple causes, particularly hypertension. Hypertensive pregnancy disorders (HPDs) are associated with future hypertension and adverse cardiac remodeling. We evaluated whether women with AF were more likely to have experienced a HPD compared with those without. Methods and Results A nested case–control study was conducted within a cohort of 7566 women who had a live or stillbirth delivery in Olmsted County, Minnesota between 1976 and 1982. AF cases were matched (1:1) to controls based on date of birth, age at first pregnancy, and parity. AF and pregnancy history were confirmed by chart review. We identified 105 AF cases: mean age 57±8 (mean±SD) years, (controls 56±8 years), 32±8 years (controls 31±8 years) after the first pregnancy. Cases were more likely to have obesity during childbearing years, and hypertension, diabetes mellitus, dyslipidemia, coronary disease, valvular disease, and heart failure at the time of AF diagnosis. Cases were more likely to have a history of HPDs, compared with controls: 28/105 (26.7%) cases versus 12/105 (11.4%) controls, odds ratio: 2.60 (95% confidence interval, 1.21–6.04). After adjustment for hypertension and obesity, the association was attenuated and no longer statistically significant; odds ratio (95% confidence interval, 2.12 (0.92–5.23). Conclusions Women with AF are more likely to have had a HPD, a relationship at least partially mediated by associated obesity and hypertension. Given the high morbidity of AF, studies evaluating the benefit of screening for and management of cardiovascular risk factors in women with a history of HPD should be performed.